Developing a Jabung Temple Booklet as a Teaching Material for Hindu-Buddhist History in High School - Adinda Meyta Dwi Ayuningtyas (Indonesian Journal of History Education, 2025)
This research and development study aimed to design, validate, and assess the feasibility of a printed booklet on Jabung Temple as a teaching material for Hindu-Buddhist history in senior high school. Using the ADDIE model, data were collected through observation, interviews, and questionnaires involving 36 tenth-grade students and history teachers at SMAN 2 Probolinggo, Indonesia. The booklet underwent validation by media experts (85.18%), material experts (83.8%), and a practitioner (98.05%), all indicating high feasibility. Student responses reached 87.29%, reflecting positive acceptance. The study concludes that the locally contextualized booklet is a viable and engaging teaching resource, supporting the integration of regional history into the curriculum. It contributes to the discourse on innovative, place-based history education in post-colonial settings.